2014
DOI: 10.1186/1471-2458-14-719
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social networks on self-management support: a metasynthesis

Abstract: BackgroundThere is increasing recognition that chronic illness management (CIM) is not just an individual but a collective process where social networks can potentially make a considerable contribution to improving health outcomes for people with chronic illness. However, the mechanisms (processes, activities) taking place within social networks are insufficiently understood. The aim of this review was to focus on identifying the mechanisms linking social networks with CIM. Here we consider network mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
225
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(239 citation statements)
references
References 48 publications
(146 reference statements)
8
225
0
6
Order By: Relevance
“…Besides Healthcare and Construction sector we found research papers reporting of similar patterned epistemic practices among other communities of expertise. Vassilev et al (2014) found that professionals in social networks are sharing knowledge and experiences in a personal community and accessing and mediating of resources. They highlighted that professionals' self-management support in social networks requires awareness of and ability to deal with network relationships: network navigation (identifying and connecting with relevant existing resources in a network), negotiation within networks (re-shaping relationships, roles, expectations, means of engagement and communication between network members), and collective efficacy (developing a shared perception and capacity to successfully perform behaviour through shared effort, beliefs, influence, perseverance, and objectives).…”
Section: Patterns Of Epistemic Practices Used By Professionalsmentioning
confidence: 99%
“…Besides Healthcare and Construction sector we found research papers reporting of similar patterned epistemic practices among other communities of expertise. Vassilev et al (2014) found that professionals in social networks are sharing knowledge and experiences in a personal community and accessing and mediating of resources. They highlighted that professionals' self-management support in social networks requires awareness of and ability to deal with network relationships: network navigation (identifying and connecting with relevant existing resources in a network), negotiation within networks (re-shaping relationships, roles, expectations, means of engagement and communication between network members), and collective efficacy (developing a shared perception and capacity to successfully perform behaviour through shared effort, beliefs, influence, perseverance, and objectives).…”
Section: Patterns Of Epistemic Practices Used By Professionalsmentioning
confidence: 99%
“…Compliance, for family care-givers, was important as the individual 460 will "not suffer" (Zoe, family, cancer) if they follow medical advice. The compliant framework, 461 however, assumes behavioural change is easy to achieve and fails to account for the difficulties and 462 complexities around achieving this change (Vassilev et al, 2014 At the core of the notion of the 'active' individual is a recognition that the 'good' self-468 manager is able to exercise agency; that is, to act freely and make their own informed decisions. Patient stakeholders considered the 'good' self-manager to engage in 'strategic non-compliance' 495 (Campbell et al, 2003) or 'rationalised non-adherence' ; that is selectively 496 applying medical advice to either suit lifestyle or minimise treatment burdens respectively.…”
mentioning
confidence: 99%
“…Recent developments point to a role for social networks in self-management support, 42 although efficacy is not yet well-established. Vassilev et al 43 suggest that social networks may effect change in self-management by improving awareness and access to network resources, adjusting social roles, relationships and communication in response to needs and through collective efficacy to achieve behavioural goals. Future research that harnesses a social network perspective to enlist and mobilise collective resources through e-health interventions may improve self-management in chronic disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…from patient self-efficacy towards collective efficacy. 43 Peer-support programmes have shown improvements in patient self-management in some chronic diseases settings, such as diabetes. For example, the ROMEO trial 27 showed a significant benefit of group education sessions for diabetes patients, scheduled quarterly over a period of two years, on knowledge, health behaviours and quality of life outcomes compared with usual care.…”
Section: Recommendations To Promote Patient Self-management: a Socialmentioning
confidence: 99%